2012
DOI: 10.3892/ijo.2012.1717
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression profile in human osteosarcoma: Role of miR-1 and miR-133b in proliferation and cell cycle control

Abstract: Abstract. miRNA profile deregulation affecting downstream signaling pathways activates endpoints that represent potential biomarkers for prognosis and treatment of tumor patients. In the past 20 years conventional therapy for osteosarcoma (OS) reached a survival plateau, highlighting the need for new therapeutic approaches. In this study, microarray unsupervised and supervised analysis identified, respectively, 100 and 40 differentially expressed miRNAs in OS samples with different grades of malignancy compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 27 publications
8
73
1
Order By: Relevance
“…We also found that cells transfected with miR-133b mimics inhibited the cell proliferation, which strongly suggests that miR-133b acts as tumor suppressor in CRC. At the same time, similar results had also been observed in osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). However, the targets of miR-133b that regulates in CRC have not been established previously.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We also found that cells transfected with miR-133b mimics inhibited the cell proliferation, which strongly suggests that miR-133b acts as tumor suppressor in CRC. At the same time, similar results had also been observed in osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). However, the targets of miR-133b that regulates in CRC have not been established previously.…”
Section: Discussionsupporting
confidence: 68%
“…However, current studies indicate a broader expression pattern of miR-133b in diverse tissues. Moreover, most of the studies showed that miR-133b was down-regulated in some human malignancies, such as osteosarcoma (Novello et al, 2013), gastrointestinal stromal tumor (Yamamoto et al, 2013), gastric cancer (Wen et al, 2013) as well as bladder cancer (Yamasaki et al, 2012). Therefore, up-regulating miR-133b or exogenously providing its analogous pharmaceutical compounds might provide effective cancer therapies for tumors.…”
Section: Mir-133b Acts As a Tumor Suppressor And Negatively Regulatesmentioning
confidence: 99%
“…In terms of osteosarcoma, abnormal expression of several miRs such as miR-206 (Bao et al, 2013), miR-34a (Wu et al, 2013), and miR-145 have been reported. Novello et al (2013) found that miR-1 and miR-133b may regulate cell proliferation of osteosarcoma cells (Novello, et al, 2013). Cai et al (2013) indicated that overexpression of miR-210 is strongly associated with large tumor size, chemotherapy resistance, positive metastasis, and decreased overall survival in pediatric osteosarcoma .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was suggested that SMAD4 is a direct target of miR-574-3p and the associated genes CDKN1A, CDKN2B as well as ID3 were strongly suppressed by miR-574-3p transfection. SMAD4 is often mutated in numerous cancers and it acts as a tumor suppressor that is involved in the regulation of the TGF-β signal transduction pathway, which negatively regulates growth of epithelial cells and the extracellular matrix (28)(29)(30)(31). Therefore, the inhibition of SMAD4 and its downstream proteins may be an important part of the mechanism of miR-574-3p in osteosarcoma.…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 99%